Xiong'an Railway Station: A Supersized Railway Station in a High Seismic Intensity Zone. Issue 2 (3rd April 2022) - Fan, Zhong; Song, Zhiwen; Zhang, Yu; Liu, Ming; Zhu, Dan
Abstract: Xiong'an Railway Station is the first super-large elevated railway station located in a high seismic intensity zone. A reinforced concrete frame structural system is adopted for the rail-bearing floor and the lower floors, while a steel structural system is adopted for the large-span roof. H-shaped steel frame beams are adopted for the elevated waiting hall, while double flange H-shaped steel beams are adopted in areas subject to great forces. Plane trusses are arranged bidirectionally between the frame beams to facilitate the laying and maintenance of equipment pipelines. The main span of the elevated waiting hall is 78 m, and variable-height box beams are adopted. The platform canopies are supported by specially shaped steel pipe columns, and the roof frame beams are connected to the tops of columns through spherical bearings. Structural innovations have been carried out in terms of semi-embedded column bases, stepped wall thickness steel pipe columns with special section shapes, large-span stiffened thin-walled box beams, and bidirectional large displacement bearings.